Some Peculiarities of Non-Newtonian Fluid Flow in to the Well Considering Spherical-Radial Model - Dadashzadeh, X.I.; Musayeva, Sh.F. (Herald of Azerbaijan Engineering Academy, 2024)
In this work, based on the laws of filtration, a model of non-Newtonian oil movement into a well is proposed taking into account the spherical-radial model. The proposed model makes it possible to describe the filtration process in a porous medium taking into account the anomalous properties of filtration fluids. The analysis shows that anomalous properties affect the indicative properties of the well and formation. Anomalous properties affect the well flow rate, pressure distribution, filtration rate, and permeability, which ultimately reduces well productivity.